Leading Change in a Complex World Transdisciplinary Perspectives - Kangas, Anni; Kujala, Johanna; Heikkinen, Anna; Lönnqvist, Antti; Laihonen, Harri; Bethwaite, Julia (Tampere University Press, 2019)
Leading Change in a Complex World : Transdisciplinary Perspectives is a transdisciplinary book offering tools for leaders, analysts and students of leadership to navigate in complex and interconnected settings. It proposes an analytical framework based on complexity, relational leadership, and dynamic change. Individual chapters examine these ideas in relation to topical societal, organisational and business challenges such as the changing global security environment, urbanisation, demographic changes, and business-government relations. The leadership roles of heads of states and societal stakeholders are analysed, and versatile leadership and management practices from conflict management to evaluation are introduced. The possibilities for change are examined through global megatrends, shifting global power blocs, changes in consumer practices, as well as those emanating from abstract concepts such as the circular economy.